Non-alcoholic fatty liver disease fibrosis score is a useful index for predicting all-cause mortality in patients with antineutrophil cytoplasmic antibody-associated vasculitis - Whang, Jeong Yeop; Park, Pil Gyu; Park, Yong-Beom; Huh, Ji Hye; Lee, Sang-Won (Frontiers in Medicine, 2023)
Background This study investigated whether the non-alcoholic fatty liver disease fibrosis score (NFS) could predict all-cause mortality during follow-up among patients with antineutrophil cytoplasmic antibody-associated vasculitis (AAV). Methods The medical records of 256 AAV patients were retrospectively reviewed. AAV patients with clinically critical chronic liver diseases were excluded. NFS was calculated using the following equation: NFS = −1.675 + 0.037 - age + 0.094 – body mass index +1.13 × impaired fasting glucose/diabetes mellitus +0.99 × aspartate aminotransferase/alanine aminotransferase ratio - 0.013 × platelet count - 0.66 × serum albumin. Results The median age was 59.0 years, and 35.2% of the patients were male. The median Birmingham Vasculitis Activity Score (BVAS), five-factor score (FFS), and NFS were 12.0, 1.0, and − 4.7, respectively. Of the 256 patients, 33 (12.9%) died. Using the receiver operating characteristic curve, the optimal cut-off of NFS for all-cause mortality was obtained as-3.97. AAV patients with NFS at diagnosis ≥ − 3.97 exhibited a lower cumulative patients’ survival rate than those with NFS at diagnosis <−3.97. The multivariable Cox analysis revealed that NFS at diagnosis ≥ − 3.97 (HR 2.232, 95% CI 1.011, 4.925) was independently associated with all-cause mortality in AAV patients. Conclusion This study was the first to demonstrate that NFS at AAV diagnosis was clinically useful in predicting all-cause mortality during follow-up, regardless of both the degree of liver fibrosis and abnormal or normal liver function results.